Becoming bulletproof : protect yourself, read people, influence situations, and live fearlessly - Poumpouras, Evy (Atria Books, 2020)
"Former Secret Service agent and star of Bravo's Spy Games Evy Poumpouras shares lessons learned from protecting presidents, as well insights and skills from the oldest and most elite security force in the world to help you prepare for stressful situations, instantly read people, influence how you are perceived, and live a more fearless life"--